Auto-organização em redes de sensores sem fio - Carlos Mauricio Serodio Figueiredo (2007)
Self-organization is an important concept that has been applied to large-scale and autonomous networksystems. Its main idea is the 'achievement of a global behavior through local interactions', which leads to networks that are less dependent on a central control, and that tend to be scalable, adaptable and, consequently, robust.In particular, Wireless Sensor Networks (WSNs) form a very active research area. WSNs are expected to have a wide applicability, and they were conceived under the self-organization paradigm due to several intrinsic characteristics. These networks consist of sensor a high number of sensing nodes interconnected by a wireless channel to perform distributed and cooperative sensing tasks. In addition to the scale, which increases the maintenance complexity, these networks tend to be very dynamic, because topological changes may be frequent due to destruction or energy depletion of nodes, inclusion of new ones, or due to the intermittent wireless communication caused by interferences or obstacles. Also, several WSN applications require the adoption of a totally autonomous behavior due to the necessity of sensing in places that are remote, inhospitable or with difficult access.Although several proposals in literature relate self-organization aspects in WSNs, sometimes implicitly, they do not provide any general and practical vision that can be used by new designs and developments. Additionally, the design process of self-organizing functions may not be trivial, because there are not formal methods of mapping desired global goals to local interaction rules. Thus, this thesis advances with two particular aspects of the concept application in the WSN domain. First, a design guideline is proposed to direct the design and the development of new self-organizing functions. Its advantage consists of a better understanding and the specification of self-organizing functions through general aspects and mechanisms. Second, a management scheme is presented, and it considers practical aspects of WSNs such that different requirements and global goals may be needed by an external application or management entity. Thus, the scheme allows the network operation in a self-organizing way in a lower level, and it also allows the action over local rules by centralized entities in a higher level, which has a wider network vision about the external needs and the network performance according to different goals.Based on the proposed general aspects, this work also gives two individual contributions regarding specific WSN functions. First, the objectivity needed in WSNs is shown through the development of a routing solution. In particular, a pro-active and a reactive self-organizing routing proposal are combined in a hybrid adaptive solution, called Multi, which extends the self-organization application in a practical approach. Second, the need of considering different self-organizing functions in an integrated design is presented in a solution, called RDC-Integrated, which considers the routing and density control functions.